COVID‐19 and obesity in childhood and adolescence: a clinical review - Carlos Alberto Nogueira‐de‐Almeida; Luiz A. Del Ciampo; Ivan S. Ferraz; Ieda R.L. Del Ciampo; Andrea A. Contini; Fábio da V. Ued (Brazilian Society of Pediatrics, 2020)
Objective: To identify factors that contribute to the increased susceptibility and severity of COVID‐19 in obese children and adolescents, and its health consequences. Sources: Studies published between 2000 and 2020 in the PubMed, MEDLINE, Scopus, SciELO, and Cochrane databases. Summary of findings: Obesity is a highly prevalent comorbidity in severe cases of COVID‐19 in children and adolescents; social isolation may lead to increase fat accumulation. Excessive adipose tissue, deficit in lean mass, insulin resistance, dyslipidemia, hypertension, high levels of proinflammatory cytokines, and low intake of essential nutrients are factors that compromise the functioning of organs and systems in obese individuals. These factors are associated with damage to immune, cardiovascular, respiratory, and urinary systems, along with modification of the intestinal microbiota (dysbiosis). In severe acute respiratory syndrome coronavirus 2 infection, these organic changes from obesity may increase the need for ventilatory assistance, risk of thromboembolism, reduced glomerular filtration rate, changes in the innate and adaptive immune response, and perpetuation of the chronic inflammatory response. Conclusions: The need for social isolation can have the effect of causing or worsening obesity and its comorbidities, and pediatricians need to be aware of this issue. Facing children with suspected or confirmed COVID‐19, health professionals should 1) diagnose excess weight; 2) advise on health care in times of isolation; 3) screen for comorbidities, ensuring that treatment is not interrupted; 4) measure levels of immunonutrients; 5) guide the family in understanding the specifics of the situation; and 6) refer to units qualified to care for obese children and adolescents when necessary. Resumo: Objetivo: Identificar fatores que contribuem para o aumento da suscetibilidade e gravidade da COVID‐19 em crianças e adolescentes obesos e suas consequências para a saúde. Fontes de dados: Estudos publicados entre 2000 e 2020 nas bases de dados PubMed, Medline, Scopus, SciELO e Cochrane. Síntese dos dados: A obesidade é uma comorbidade altamente prevalente em casos graves de COVID‐19 em crianças e adolescentes e o isolamento social pode levar ao aumento do acúmulo de gordura. Tecido adiposo excessivo, déficit de massa magra, resistência à insulina, dislipidemia, hipertensão, altos níveis de citocinas pró‐inflamatórias e baixa ingestão de nutrientes essenciais são fatores que comprometem o funcionamento dos órgãos e sistemas no indivíduo obeso. Esses fatores estão associados a danos nos sistemas imunológico, cardiovascular, respiratório e urinário, juntamente com a modificação da microbiota intestinal (disbiose). Na infecção por SARS‐CoV‐2, essas alterações orgânicas causadas pela obesidade podem aumentar a necessidade de assistência ventilatória, risco de tromboembolismo, taxa de filtração glomerular reduzida, alterações na resposta imune inata e adaptativa e perpetuação da resposta inflamatória crônica. Conclusões: A necessidade de isolamento social pode ter o efeito de causar ou agravar a obesidade e suas comorbidades e pediatras precisam estar cientes desse problema. Diante de crianças com suspeita ou confirmação de COVID‐19, os profissionais de saúde devem 1) diagnosticar o excesso de peso; 2) aconselhar sobre cuidados de saúde em tempos de isolamento; 3) fazer a triagem de comorbidades, garantindo que o tratamento não seja interrompido; 4) medir os níveis de imunonutrientes; 5) orientar a família respeitando as especificidades da situação; e 6) encaminhamento a unidades qualificadas para cuidar de crianças e adolescentes obesos, quando necessário.